Enhancing harvested rainwater productivity in North-West Himalayas by irrigation scheduling and organic manuring - BHARDWAJ1, A. K.; KATOCH2, K. K.; NAGARAJA, M. S. (Journal of Soil and Water Conservation, 2021)
A two-year study was conducted to evaluate the productivity of rainwater, harvested in an earthen dam, for vegetable crop production under wet temperate climate at Palampur in North-West India. Okracabbage- potato cropping sequence was tested for total water use with harvested pond water. The water use efficiency using irrigation scheduling at 0.6, 0.8 and 1.0 IW/CPE (irrigation water / cumulative pan evaporation) ratios and at matric suction of 300 and 450 cm of water were the tested variables. Along with irrigation, chemical fertilizer and farmyard manure treatments which included chemical fertilizers alone (F1), recommended chemical fertilizers + farmyard manure (F2), and double the recommended rate of farmyard manure (F3) were also evaluated for their effects on soil quality parameters. The study revealed that at least 60 cm of rainwater harvesting is needed to sustain okra-cabbage-potato crop sequence in the region. For irrigation in cabbage and potato, scheduling irrigation with IW/CPE (Irrigation Water/ Cumulative Pan Evaporation) ratio of 1.0 and matric suction of 300 cm water was most suitable, as highest water use efficiency was obtained using these schedules. Irrigation scheduling coupled with increased rates of FYM improved soil parameters with respect to moisture retention, available water capacity, porosity, infiltration and hydraulic conductivity